Controlling antibiotic resistance in the community - Wilson, Peter (Henry Stewart Talks, 2009)
Risk factors and control of multi-resistant pathogens, Community-acquired MRSA, Multi-drug resistant tuberculosis, Extended spectrum beta-lactamase producing Gram negative bacteria, Vancomycin resistant enterococci, Antibiotic stewardship in primary care
Reviewed at 2015/07/24